2014
DOI: 10.1007/s12032-014-0396-7
|View full text |Cite
|
Sign up to set email alerts
|

Topo2A as a prognostic biomarker for patients with resectable esophageal squamous cell carcinomas

Abstract: Topoisomerase 2α (Topo2A) is a key enzyme in replication. It functions as a cell proliferation and cell cycle-specific marker and it is identified mainly in the interphase nuclei of proliferating cells. Many studies have shown that Topo2A protein expression is up-regulated in various cancers including esophageal cancer. However, to date, no studies have adequately addressed the prognostic value of Topo2A in patients with resectable esophageal squamous cell carcinoma (ESCC). Therefore, we conducted a large-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…TOPO2A is expressed in 48.7% of EC tumors with 24.14% of EC tumors being pathologically considered overexpressed (88). TOPO2A has also been deemed a prognostic factor in EC patients as tumors with no TOPO2A expression survived almost a year longer than patients with low to high TOPO2A expression (89). Also, TOPO2A expression in esophageal tumors has been associated with worse cellular differentiation and more perineural invasion—illuminating a potentially greater role for anthracyclines in suppressing the aggressiveness of TOPO2A positive tumors (89).…”
Section: Discussionmentioning
confidence: 99%
“…TOPO2A is expressed in 48.7% of EC tumors with 24.14% of EC tumors being pathologically considered overexpressed (88). TOPO2A has also been deemed a prognostic factor in EC patients as tumors with no TOPO2A expression survived almost a year longer than patients with low to high TOPO2A expression (89). Also, TOPO2A expression in esophageal tumors has been associated with worse cellular differentiation and more perineural invasion—illuminating a potentially greater role for anthracyclines in suppressing the aggressiveness of TOPO2A positive tumors (89).…”
Section: Discussionmentioning
confidence: 99%
“…Wittmann et al (23) confirmed that the high expression of TOP2A was associated with tumor metastasis and death outcome by analyzing 102 cases of nephroblastoma. A large-scale retrospective study has demonstrated that TOP2A high expression is associated with poor differentiation and neural invasion of esophageal cancer, and is also an independent risk factor affecting the prognosis of esophageal cancer (24). De Resende et al (25) have reported that high expression of TOP2A protein is associated with severe lymphatic vascular invasion and a low relapse-free survival rate in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the previously mentioned role of TopoIIα in cell division and its increased expression in the G2/M phase of the cell cycle, immunohistochemical staining for TopoIIα may be useful in the determination of cell proliferation, and eventually malignant transformation (911). Previous studies have considered TopoIIα as a prognostic factor in patients with esophageal squamous cell carcinomas, breast cancer, clear cell renal cell carcinoma and nasopharyngeal carcinoma (1215). …”
Section: Introductionmentioning
confidence: 99%